The impact of rehabilitation on the quality of life of patients with vulvovaginal atrophy - D. M. Ampilogova; A. G. Solopova; D. V. Blinov; G. K. Bykovshchenko; S. V. Khlopkova; A. E. Ivanov (Акушерство, гинекология и репродукция)
Aim: to evaluate the impact of rehabilitation on various components of quality of life (QoL) in patients with vulvovaginal atrophy (VVA).Materials and Methods. A prospective comparative controlled longitudinal study involved 350 patients with VVA, divided into groups based on the type of menopause: surgical (n = 140) and natural (n = 140), with a control group of 70 women without VVA. Patients were further subdivided into those receiving complex "active" (groups 1A, 2A) and "passive" (groups 1B, 2B) rehabilitation. The study included 6 visits over 24 months, assessing QoL using the Female Sexual Function Index (FSFI), Hospital Anxiety and Depression Scale (HADS), Modified Menopausal Index (MMI), Well-being, Activity, Mood questionnaire (WAM), Magnesium Deficiency Questionnaire (MDQ), and the Assessment Test of Magnesium Deficiency (ATMD).Results. Women with surgical menopause had severe sexual dysfunction initially. Complex "active" rehabilitation significantly improved sexual function over time compared to "passive" rehabilitation. Surgical menopausal women had higher initial levels of anxiety and depression. "Active" rehabilitation significantly reduced these levels, reaching normal values within the first year. Patients with surgical menopause exhibited more severe menopausal symptoms. "Active" rehabilitation led to significant reductions in these symptoms, improved well-being, activity, and mood more significantly than "passive" rehabilitation, particularly in the first year. Complex "active" rehabilitation normalized magnesium deficiency indicators within three months, maintaining normal levels throughout the study.Conclusion. Comprehensive "active" rehabilitation significantly improves sexual function, reduces anxiety and depression, alleviates menopausal symptoms, and enhances overall well-being in women with VVA, especially those in surgical menopause. Personalized rehabilitation programs are crucial for enhancing QoL in these patients.